NEGARA DALAM PERSPEKTIF PLATO - Hakim, Abdul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2010)
According to Plato, the aim of establishing a state is to achieve pleasuresand happiness for all citizens based on justice, wisdom, courage and soli-darity. To attain the aim, the citizens should have knowledge, especiallyknowledge of virtues, and try to realize them in their daily lives. The king,as the top leader of the state, should have the highest level of the knowledge.The king should be a philosopher.